Effect of reinforced fiber on morphology of Si phases in Al2O3/AI-Si alloy composite - Zheng LIU; Xiaomei LIU; Yinglu ZHU (China Foundry, 2005)
Alumina/aluminum-silicon alloy composite is manufactured by squeeze casting. The effect of the reinforcement on the morphology of the silicon phase in aluminum-silicon alloy is studied. The results indicate that an alumina fiber can serve as propitious sites for the heterogeneous nucleation of the silicon phase, and the primary silicon in the composite can nucleate on the surface of the fiber. The fiber in the composite can trigger twin during the coupled growth of the aluminum-silicon eutectic and lead to modification of the eutectic silicon near the fiber.